Ocular hypotensive efficacy and safety of once daily carteolol alginate. Issue 8 (1st August 2001) - Demailly, Philippe; Allaire, Catherine; Trinquand, Claude
Abstract : BACKGROUND/AIM: Carteolol is a β adrenoceptor antagonist used topically to reduce intraocular pressure, typically twice daily. In an effort to provide a once daily dosing regimen, carteolol was formulated with 1% alginic acid. The objective of this study was to evaluate the efficacy and safety of carteolol alginate solution in comparison with standard carteolol solution. METHODS: This was a double masked, parallel group, multicentre study. Patients with ocular hypertension or open angle glaucoma (n=235) were randomly assigned to receive either carteolol alginate four times daily or standard carteolol solution, twice daily. The masking was maintained through the use of a vehicle in the evening for the alginate group. Patients were evaluated at baseline, 15, 60, and 120 days. RESULTS: At 0900 (presumed trough) on day 60, mean reductions in intraocular pressure (IOP) from baseline were 6.09 (SD 2.97) and 6.09 (3.18) mm Hg for the standard carteolol and alginate, respectively. At 1100 (presumed peak), mean reductions were 6.51 (2.53) and 6.47 (2.76) mm Hg, respectively. Results were similar at other times (day 15 and day 120). The most common side effect was transient stinging on instillation of drops, which did not differ significantly between groups. There were no differences of note in other ocular or systemic signs or symptoms. CONCLUSION: The new alginate formulation of carteolol 2% given once daily was as effective as standard carteolol 2% given twice daily with no meaningful differences regarding safety.